2006
DOI: 10.1089/dna.2006.25.253
|View full text |Cite
|
Sign up to set email alerts
|

TLR9-Independent Activation of B Lymphocytes by Bacterial DNA

Abstract: The intracellular Toll-like receptor 9 (TLR9) is unique in its ability to recognize single-stranded DNA unmethylated at CpG motifs. Work from this laboratory showed that plasmid DNA is spontaneously internalized in B lymphocytes. This event is followed by the upregulation of costimulatory molecules and the acquisition of antigen presenting function by these cells. However, it is not known whether this phenomenon depends on TLR9. Because of the relevant role played by DNA-based drugs in immunotherapy and vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…We found that when compared with LPS or CpG ODN, pDNA induced a similar magnitude of proliferation as control ODN (Fig. 3), confirming that pDNA is not mitogenic for B lymphocytes (31,32). In contrast, B lymphocytes incubated with ␥1E␣ 3 KDEL or ␥1E␣ 3 pDNA did up-regulate the costimulatory molecule CD86 (data not shown), another marker of B cell activation.…”
Section: Analysis Of the Cd4 T Cell Response In Vivosupporting
confidence: 52%
“…We found that when compared with LPS or CpG ODN, pDNA induced a similar magnitude of proliferation as control ODN (Fig. 3), confirming that pDNA is not mitogenic for B lymphocytes (31,32). In contrast, B lymphocytes incubated with ␥1E␣ 3 KDEL or ␥1E␣ 3 pDNA did up-regulate the costimulatory molecule CD86 (data not shown), another marker of B cell activation.…”
Section: Analysis Of the Cd4 T Cell Response In Vivosupporting
confidence: 52%
“…However, other workers have described surface expression of TLR9 in various types of cells (6,7,9,18,27). Furthermore, studies using chloroquine to inhibit endosomal acidification have produced different results; some investigators have observed inhibition of TLR9 signaling (1,10,30), and other workers have observed no effect, indicating that there may be an alternate pathway (8,18). In our study, TLR9 was shown by flow cytometry, immunofluorescence, and biotinylation of surface proteins to be expressed on the surface of intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…They further demonstrated that dsDNA-transfected MEFs were protected against HSV infection in vitro. Cortez-Gonzalez et al observed that B cells transfected with ds plasmid DNA upregulated co-stimulatory molecules in a TLR9-independent manner, enabling these B cells to be potent antigen-presenting cells [15]. The physiological role of TLR9-independent recognition of dsDNA has been suggested to be as an endogenous T helper 1 (Th1)-type adjuvant [7,38]; however, roles in infection, autoimmune diseases, allergy and cancer, as well as in DNA-based immunotherapy, should be clarified by future studies.…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, double-stranded (ds)DNA derived not only from microbes but also from host cells activates the innate immune system in a sequence-independent manner when either it is introduced into the cytosol [6,7] or its homeostatic clearance is hampered [8]. This was not mediated by TLR (9), but instead by an as-yet-undefined DNA recognition machinery that activates both immune and non-immune cells to produce type I interferons (IFNs), cytokines and chemokines, as well as by the upregulation of co-stimulatory molecules [9][10][11][12][13][14][15] (Figure 1). Therefore, during infection and/or tissue damage, DNA derived from pathogens and damaged host cells might regulate both innate and adaptive immune responses.…”
Section: Introductionmentioning
confidence: 99%